Editorial: Introducing the special issue on “Challenges, opportunities, and directions in accounting” - Major, M. J. (Accounting and Management Review, 2022)
This special issue signals the re-birth of the Revista de Contabilidade e Gestão, which following the appointment of a new Editor-in-Chief and of new Associate Editors in June 2021 by the Chairwoman of Ordem dos Contabilistas Certificados(OCC), has been renamed as the Accounting and Management Review. As earlier, the Accounting and Management Review seeks to be a platform between academics and practitioners in public and private sectors, fostering high quality research in accounting and management fields that enhances understanding on the nature and implications of accounting and managerial practices. With the relaunch of the journal two additional concerns related to the internationalization of authors and the scope of research, as well as the contribution of articles to the promotion of the good of society and the betterment of the world have been embraced by the new Editorial Team. In so doing there is the explicit understanding that accounting is neither a neutral device nor a mere technique, but a ubiquitous practice that shapes the moral order of world and the way that the every-day life of organizations and individuals is framed; and that the journal should not confine accounting research to any specific country or region, nor to any determined methodology or theoretical lens if it is to produce global impact and to contribute to a changing world.